Status Kritis Dua Jenis Badak di Indonesia - Sadjudin, Haerudin R.; Syamsudin, Mochammad; Ramono, Widodo Sukohadi (Al-Kauniyah: Jurnal Biologi, 2013)
There are five species of rhinoceros in the world, two types of African (Diceros bicornis and Ceratotherium simum) and three species in Asia (Rhinoceros unicornis, Rhinoceros sondaicus and Dicerorhinus sumatrensis). Indonesia has two types, namely: the Javan rhino (Rhinoceros sondaicus Desmarest, 1822) and the Sumatran rhino (Dicerorhinus sumatrensis Fischer, 1814).Both types of rhino in Indonesia is not endemic wildlife, but it is a species relich; formerly spread is very wide, but now in addition to the steadily declining population is also more limited distribution. This happens because it is caused by the conversion of forests as a habitat for rhinos, plantations, settlements, and exploitation of space for various purposes. Hunting of two species of rhinoceros also has a long history, so that a distribution in some places have been lost; as well as the habitat that has been designated as a conservation area too, the population in the last 35 years continues to decline. Therefore both the rhino species has been categorized by the IUCN (International Union of Conservation of Nature and Natural Resources) as critical or threatened species (Critical Endangered Species), highly endangered species. Due to the critical status, then efforts were made to save him. But it seems these efforts have not maximized, because not all potential or the ability Â multi-party support to carry out rescue from extinction.